Kekerasan Simbolik Dalam Tradisi Perkawinan Masyarakat Tolaki Sulawesi Tenggara - Asliah Zainal; Sudarmi Suud (Institut Agama Islam Negeri Kendari, 2018)
The position of customary institutions in traditional societies has two faces; be a protector and solution for the community, but can also be a dominant and even compelling force. This study will examine the marriage traditions of the Tolaki community that move between apparent compromise and potential conflict. Indigenous marriages implicitly indicate a form of symbolic violence that constructs false compromise in Tolaki society as well as potential latent conflicts. Symbolic violence can be found in several forms, namely injustice in the opportunity to marry women from any group; and rejection of procedures and marriage procedures. This condition is caused by social differences in the community; there is no legitimacy of the crime and the same opportunities; differences in interests between various parties; and the dominance of the indigenous elite. However, the marriage practices of the Tolaki community bring change with the loosening of the system and the social structure of the Tolaki community which was originally